Second grader students in WhatsApp group e-Learning process - Nurul Nuraeni (Mitra Palupi, 2021)
Background: Learning supports is needed for being more effective and efficient in the process of students’ learning. In learning through WhatsApp, in fact students feel less interested because in WhatsApp learning is not interesting at all, with learning through WhatsApp or E-Learning many students hold smartphones every day but do not participate in this WhatsApp learning or learning E-learning. Purpose: This study aims to determine the impact of WhatsApp group learning on distance learning activities of SDN Cijeruk 01 students, especially in grade 2. Design and methods: This type of research is using a descriptive qualitative approach. The research subjects were parents or guardians of grade 2 elementary school students. Using triangulation validation between researchers with interview techniques. Results: The results of this study indicate that SDN Cijeruk 01 in e-learning using WhatsApp group is not very effective and in the learning process students are accompanied by parents.